FAMILY SOCIAL CONTROL TO BULLYING CULTURE IN HIGH SCHOOL - Karnadi Karnadi (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
This research goals is to given the descriptive brief about the form of interaction that applied between social agents, especially the senior and junior in High School (SMA). The research itself told about the transmition of bullying culture that happen in some High School in Jakarta, which done by seniors to their juniors. Also, this research will happen to know how the effectiveness of social crime prevention which applied by family agents as a primary social agent that should prevent any form of violence at school.